Mammalian flavin-containing monooxygenases - Rettie, Allan (Henry Stewart Talks, 2010)
Flavin-containing monooxygenases (FMOs), FMO structure, function and regulation, Role of FMOs in drug metabolism and drug toxicity, Methods for distinguishing between FMO and P450 catalysis
Updated at 2015/09/30